2021
DOI: 10.1055/s-0041-1726017
|View full text |Cite
|
Sign up to set email alerts
|

The Association of Vision, Hearing, and Dual-Sensory Loss with Walking Speed and Incident Slow Walking: Longitudinal and Time to Event Analyses in the Health and Retirement Study

Abstract: With the aging of the population, vision (VL), hearing (HL), and dual-sensory (DSL, concurrent VL and HL) loss will likely constitute important public health challenges. Walking speed is an indicator of functional status and is associated with mortality. Using the Health and Retirement Study, a nationally representative U.S. cohort, we analyzed the longitudinal relationship between sensory loss and walking speed. In multivariable mixed effects linear models, baseline walking speed was slower by 0.05 m/s (95% c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 37 publications
0
5
0
Order By: Relevance
“…Their results showed that the magnitude of VO 2 max improvement was affected by the initial training status [94]. Beside the general decline in VO 2 max, several aging-related changes may negatively affect high-altitude performance in the elderly, e.g., the development of cardiovascular and pulmonary diseases [88], loss in vision and hearing [95] or changes in blood rheology [96]. In summary, altitude related changes in VO 2 max (and SpO 2 max) may become increasingly important in the elderly due to the declining VO 2 max with aging.…”
Section: Effects Of Agementioning
confidence: 99%
“…Their results showed that the magnitude of VO 2 max improvement was affected by the initial training status [94]. Beside the general decline in VO 2 max, several aging-related changes may negatively affect high-altitude performance in the elderly, e.g., the development of cardiovascular and pulmonary diseases [88], loss in vision and hearing [95] or changes in blood rheology [96]. In summary, altitude related changes in VO 2 max (and SpO 2 max) may become increasingly important in the elderly due to the declining VO 2 max with aging.…”
Section: Effects Of Agementioning
confidence: 99%
“…Furthermore, it has been reported that VI is associated with a slower walking speed and shorter one-leg standing time [ 9 ]. Further, compared with SSI, DSI increases the risks of weak handgrip strength [ 7 ] and slow walking speed to greater extents among older adults [ 32 ]. However, it has been difficult to quantify the effect of DSI on physical function in older adults because most previous studies evaluated sensory impairment and physical function via a self-report method, which could be subjective [ 7 , 19 , 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…Several inherited disorders have been described that share impairment of both vision and hearing, a condition known as dual-sensory impairment or DSI. Individuals with impairment in one sensory organ tend to use the functioning organ to compensate in their daily functioning; however, having impairment of both sensory organs can have significant, and often synergistic, detrimental effects on patient's quality of life and physical functioning [193]. This has been shown in older adults where sensory impairment is typically insidious, which may give patients time to adapt.…”
Section: Discussion and Future Directionmentioning
confidence: 99%